2017
DOI: 10.2174/1573406412666160920091146
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Analgesic and Anti-ulcerogenic Activities of Novel bis-thiadiazoles, bis-thiazoles and bis-formazanes

Abstract: In this context, we synthesize new derivatives of bis-thiazoles and bis-1,3,4-thiadiazoles as anti-inflammatory, anti-ulcerogenic and analgesic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…1,2‐Phenylene‐bis‐thiourea 54 was reported to react with hydrazonoyl chloride 137 in refluxing benzene and triethylamine and afforded the 1,2‐phenylene‐bis ‐ (1,3,4‐thiadiazol‐2‐ylidene) derivative 138 in good yields (Scheme ) .…”
Section: Reactions Of Bis‐thioureasmentioning
confidence: 99%
“…1,2‐Phenylene‐bis‐thiourea 54 was reported to react with hydrazonoyl chloride 137 in refluxing benzene and triethylamine and afforded the 1,2‐phenylene‐bis ‐ (1,3,4‐thiadiazol‐2‐ylidene) derivative 138 in good yields (Scheme ) .…”
Section: Reactions Of Bis‐thioureasmentioning
confidence: 99%
“…Owing to numerous pharmacological and biological applications thiazole derivatives have gained tremendous attention in the scientific community. Thiazole is reported in literature as antibacterial, 1 antiviral, 2 anti-inflammatory, 3 antifungal, 4 antitubercular, 5 antitumoral, 6 anti-HIV 7 and antioxidant agent. 8 Moreover, numerous marketed drugs possess thiazole scaffold as an active group.…”
Section: Introductionmentioning
confidence: 99%
“…Many patents have been registered for thiazole compounds with antimicrobial activity [10,11]. It has been demonstrated that the design and synthesis of organic compounds containing more than one thiazole ring unit enhanced their therapeutic activities [12,13,14,15]. Thus, many researchers have become interested in the synthesis of molecules containing more than one thiazole moiety [16,17].…”
Section: Introductionmentioning
confidence: 99%